Serum total IgG and IgG4 levels in thyroid eye disease - Sy A; Silkiss RZ (International Medical Case Reports Journal, 2016)
Aileen Sy, Rona Z Silkiss Department of Ophthalmology, California Pacific Medical Center, San Francisco, CA, USA Purpose: To investigate the relationship between immunoglobulin G (IgG)4-related disease (IgG4-RD) and thyroid eye disease (TED) with respect to IgG levels. Patients and methods: A retrospective review of total IgG, IgG subclass, and thyroid stimulating immunoglobulin (TSI) levels in 24 patients with TED. Results: Five patients (20.8%) demonstrated serum IgG4 levels consistent with IgG4-RD without any additional systemic disease. Total IgG and IgG subclass levels were found to be an inadequate proxy for TSI elevation. Conclusion: There may be a subtype of TED patients with elevated IgG4 in the absence of IgG4-RD systemic findings. Keywords: thyroid eye disease, IgG subclass, IgG4, Graves’ disease, Graves’ ophthalmopathy, IgG4-RD